The Influence of Class VII Science Subject Teaching Materials in Improving Critical Thinking - Eka Sriwahyuni; Tri Putri Wahyuni; Atyka Trianisa; Ristina Mirwanti; Dian Permata Sari (CV. Get Press Indonesia, 2024)
This educational process does not only focus on knowledge transfer; it also develops a wide range of individual potential, including academic abilities, relationships, talents, aptitudes, physical abilities, and the arts. Progressivism education is essential to the understanding and implementation of true education in Indonesia. Progressivism education educates students to face and solve problems in social life. This shows how important education is to produce people who are beneficial to society and the country (Sulkifly, 2020). This research uses a quantitative approach and is classified as quantitative descriptive research. This research method is conducted by collecting numerical data. This process of collecting and analyzing data is known as research design or research design. This indicates that the research includes planning and conducting it. The design starts with observing and evaluating known research until further evidence is needed. In the research design, a pre-test and post-test control group was used. This test is done with pearson correlation or by comparing r count with r table. Data validity can be seen if rcount> rtable with 5%. If rtable < rcount then it is said to be valid. The results of the T table test show that the t count obtained is 14.450 has a significance value of 0.000, which indicates that the seventh grade science subject matter has a significant effect on improving students' critical thinking skills. Based on the results of hypothesis testing, F table obtained 208.806 or greater than F table (208.806 greater than 4.351).